Grønland som del af den bibelske fortælling – en 1700-tals studie - Kjærgaard, Kathrine (Kirkehistoriske Samlinger, 2010)
Summary The article describes how the Danish-Norwegian and German missionaries’ ideas about Greenland as part of the biblical narrative, utilizing several theological forms of communication and practice, were disseminated to the population, so that by the end of the 1700s an imagined national community had been created. For the missionaries on Greenland, as for most other people in the 18th century, the Bible was a historically accurate narrative about the world, which encompassed all of world history from the Creation to the End of Days. The Bible was not just a true story about the past, however. It was also a true story about the present and the future. The missionary project in Greenland was seen in light of the Old Testament prophecies of the conversion of all pagans. The conversion of the Greenlanders was predicted in the Old Testament. The Greenlanders originated from Noah’s son, Shem, and were thus a people with roots in the Old Testament Diaspora following the Flood and the Tower of Babel. In the Greenlanders’ language, name-giving ceremonies and customs, the missionaries found clear traces of their Middle East origins, just as they found the divine law inscribed in their hearts. As for the missionaries, they lived their lives in the light of divine providence, and with typological interpretations, they added their own lives and works to the biblical narrative. The missionaries told the Greenlanders about the Bible’s world historical construction and about their place in this history. They told them of the Creation, the Fall from Grace, the Flood, about Noah’s Ark and the dispersion of the worlds’ peoples, and they told them of man’s redemption, about the Resurrection and about eternal life. The missionaries, of whom several were significant naturalists, constantly supported their teachings with references to the Greenlandic nature and reality, which so convincingly illustrated God’s special care: the sun which disappeared in the winter and returned in the summer to melt the ice, so that the whales and seals could make their way toward land and provide the people with food, clothing, tenets and boats. All together so wisely organized that all species were maintained without their destroying each other. The 18th century physico-theological thinking in Denmark-Norway had a strong following among the Greenland missionaries. Communication took place not only with words. In the early days, the Word was not in the missionaries’ power, for Greenlandic in 1721 was an unknown, un-described language, just as there existed no Greenlandic written language. When Hans Egede, the first Danish-Norwegian missionary in Greenland, realized that he could not speak with the population, he would resort to showing some visitors a large picture of the blessed Jesus. Egede discovered that pictures had power, and the mission, in line with what we know from the French Jesuit mission in North America, took a ‘visual turn’. Hans Egede not only showed theGreenlanders illustrations from books, but together with his son Poul, composed his own illustrations of the Garden of Eden, Jesus’ birth, the miracles of Christ, the Resurrection, and other key biblical scenes. Circumstances thus compelled Hans Egede’s mission into a pictorial mission, and it remained a pictorial mission, even after he had obtained power over the Word. This visual emphasis has characterized the Greenlandic church and the Greenlandic people up to the present. By the mid-18th century, when churches had been constructed, an effort was immediately made to procure good altar illustrations. The result was that several splendid artworks came to Greenland, including a rare Rubens copy of ‘Jesus before Pilate’ from the 1780s. In the beginning was the picture, then came the words and the sounds: psalms, church bells and trumpets. Across the landscape arose churches, towers, missionary stations and cemeteries. Veritable resurrection landscapes arose which symbolically expressed the morning of the resurrection. This tendency was especially pronounced among the German Moravians (in Greenland from 1733), who practiced funeral ceremonies where the deceased, in a procession accompanied by trumpets, were led from the ‘lower congregation’ to the ‘upper congregation’ so that together with those who had gone before, they would await the morning of the resurrection. The article demonstrates how the Greenlanders not only became Christianized, but also how they embraced the biblical imagination and appropriated the Bible as their own history. As they assimilated the idea of God and the Creation, they came to believe that God had created Greenland and the Greenlanders. Some believed, perhaps, that God has been a bit petty and not done His work so well as in other places, because Greenland was not so fertile as, for example, Denmark. On reflection, however, they realized that Greenland contained all they ever needed: seals, whales, timber that drifted ashore. When shellfish were found in the mountains, it was seen as testimony that the sea had covered the mountains, as proof of the Flood. In this way, the country below the Arctic Circle became living proof of the biblical story. When the missionary Poul Egede, during a trip to Copenhagen, stopped in Norway, his Greenlandic traveling companion spotted thorny bushes and said, ‘No doubt, here are the same kind of trees that tormented our saviour’. The Bible and the idea that the Greenlanders were a people under God’s care became an integral part of Greenlandic identity and worldview. With the Children of Israel as a role model, the image was created of a Greenlandic people. Translation into English by Steven Sampson